2018
DOI: 10.1088/1757-899x/288/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Web Scraping and Naïve Bayes Classification for Job Search Engine

Abstract: Abstract. Many organisations (government of non-government) use websites to share information of new recruitment for the workers. This information overflows on thousands of sites with various attributes and criteria. However, this availability forms a complex puzzle in the selection process and lead to inefficient runtime. This study proposes a simple method for job searching simplification through a construction and collaboration of web scraping technique and classification using Naïve Bayes on search engine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…Previous studies on algorithms of classification have proven that Naïve Bayes is one of the best algorithms in comparison with the other ones such of Decision Tree, Naïve Bayes, and K-NN. It has also been found that accuracy and speed are the most supporting and helpful features of the algorithm in classifying data [12]. The advantage of Bayesian classifier is that it requires small training data set for classification.…”
Section: Naïve Bayes Classification Approachmentioning
confidence: 99%
“…Previous studies on algorithms of classification have proven that Naïve Bayes is one of the best algorithms in comparison with the other ones such of Decision Tree, Naïve Bayes, and K-NN. It has also been found that accuracy and speed are the most supporting and helpful features of the algorithm in classifying data [12]. The advantage of Bayesian classifier is that it requires small training data set for classification.…”
Section: Naïve Bayes Classification Approachmentioning
confidence: 99%
“…Expert systems are systems that process data in an organized manner [8], which seeks to adapt human knowledge to a computer, so that the computer can solve problems as is usually done by experts [9]. Based on many research results, the expert system has a very good ability in decision making, the system has advantages in terms of: good data accessibility, efficient in time [10], accurate [11], support decisions appropriately [12], more economical [13], broad accessibility [14], improving user understanding [15], improving productivity [16], presenting data and information well [17], and in certain cases can be utilized as data storage media [18].…”
Section: System Designmentioning
confidence: 99%
“…DSS is the part of information system for supporting decision for decision making. Refers to several research, an information system has a high capability in decision making, the system has an accurate data accessibility and efficient run-time [10], high accuracy [11], and to support a proper decision [12], low cost [13], extended accessibility [14], intensify user knowledge, increase productivity [15], provide a better data and information [16], and in the certain cases are potentially used as data storage [17].…”
Section: Introductionmentioning
confidence: 99%